Molecular characterization of piper species usiing RAPD technique - Murugan C (Department of Plantation Crops and Spices, College of Horticulture, 2002)
The study on "Molecular characterization of Piper species using RAPD techniques" was conducted in the Department of Plantation Crops and Spices and CPBMB, College of Horticulture, Vellanikkara, Thrissur from December, 1999 to August, 2001. Material included 13 species/accessions of the genus Piper including Piper nigrutn Linn. These were analysed with 20 selected oligomer decamer primers using PCR technique and agarose gel electrophoresis. The selection of ideal DNA isolation technique was done based on observations of purity of bands, quality of the DNA bands and quantity of DNA recovered. The protocol of Edwards et al. (1991) was selected for DNA isolation with additional step of chloroform-isoamyl alcohol treatment. Fifty decamer primers were screened using DNA. of P. nigrum and 20 were selected based on the number of bands produced, reproducibility of the bands and distinctness of the RAPD profile. RAPD profile of the 13 species of Piper were compared for genetic similarity index (using Jaccard's coefficient), with all 20 selected primers separately. Pooled similarity of the twenty primers put together was found out for 9 species which gave amplification for all the 20 selected primers. The results of pooled analysis was subjected to cluster analysis (SAl-IN) and phenetic dcndrogram was constructed employing UPGMA. Four clusters were obtained, comprising of two accessions of P. nigrum In the first, two accessions of P. longum in the second, P. colubrinutn and P. attenuatum forming the third cluster and P. chaba, P. belle and P. arboreum forming the fourth.